Analisis Penerapan Itil V3 pada Layanan Helpdesk dalam Manajemen Layanan Ti: Studi Literatur - Ayu Mutma Ina Agustin; Viona Violetta; Nickytha Nunik Rindi Aryani; Eriene Dheanda Absharina (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
The rapid development of information technology has encouraged organizations to provide efficient and high-quality IT services to support operational activities and user needs. One of the main services in IT service management is the helpdesk, which functions to handle incidents, service requests, and provide technical support to users in an efficient manner. However, in practice, helpdesk services often face various challenges such as slow response times to incidents, lack of systematic documentation, and the absence of clear standard operating procedures in managing IT services. These issues can lead to a decline in service quality and user satisfaction. Therefore, a framework is needed to help improve the quality of IT services, one of which is the Information Technology Infrastructure Library (ITIL) V3. This study aims to analyze the implementation of ITIL V3 in helpdesk services within IT service management. The method used in this research is a literature review by examining various relevant journals and previous studies. The results show that the implementation of ITIL V3, particularly in the Service Operation domain. such as incident management and helpdesk, can improve service efficiency, accelerate incident handling time, and enhance overall IT service quality. In addition, ITIL implementation also contributes to process standardization and increased user satisfaction. Thus, ITIL V3 can be an appropriate solution to improve helpdesk service performance and support more structured and sustainable IT service management.